1997
DOI: 10.1161/01.atv.17.12.3602
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the P2Y 2 Purinoceptor in Intimal Lesions of the Rat Aorta

Abstract: Extracellular nucleotides, particularly ATP, are involved in the modulation of arterial vasomotricity via P2 purinoceptors present on smooth muscle and endothelial cells. These nucleotides could also be implicated in the smooth muscle cell hyperplasia observed in intimal lesions. In this study, we tried to define the potential role of the P2Y2 (P2u) purinoceptor by studying its expression in normal and balloon-injured rat aortas. The cloning of a rat P2Y2 cDNA from a rat smooth muscle cell cDNA library made it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
68
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 36 publications
4
68
0
Order By: Relevance
“…Vascular cells have been shown to express metabotropic P2Y and ionotropic P2X receptors (5,8). It has been reported that P2Y 2 receptors are upregulated in cells of rat intimal lesions following balloon angioplasty (9). Our recent studies showed that placement of a silicone collar around the rabbit carotid artery promoted upregulation of P2Y 2 receptors in vascular smooth muscle cells and endothelium (10).…”
mentioning
confidence: 66%
“…Vascular cells have been shown to express metabotropic P2Y and ionotropic P2X receptors (5,8). It has been reported that P2Y 2 receptors are upregulated in cells of rat intimal lesions following balloon angioplasty (9). Our recent studies showed that placement of a silicone collar around the rabbit carotid artery promoted upregulation of P2Y 2 receptors in vascular smooth muscle cells and endothelium (10).…”
mentioning
confidence: 66%
“…The P2Y 2 R is up-regulated in a variety of tissues in response to injury or stress, including the vasculature (33). We have shown that stress-activated up-regulation of P2Y 2 Rs in vascular endothelium in vivo increases the expression of adhesion molecules, monocyte adherence, and transendothelial migration (34,35), suggesting that P2Y 2 Rs for cytokine-like nucleotides play a role in endothelial-dependent inflammation.…”
mentioning
confidence: 87%
“…Although the P2Y 2 R is normally expressed in monocytes, neutrophils, and other immune cells (13), recent studies have shown that the P2Y 2 R is up-regulated in epithelial and vascular tissue in response to injury or stress (14). Upon activation, the P2Y 2 R mediates a variety of biological functions, including mitogenesis, angiogenesis, vasodilatation, chemotaxis, and inflammation (15,16).…”
mentioning
confidence: 99%